Utilizing Waste from the Natural Resources of Harapan Island to Become Kitchen/Pantry Decoration Elements in Residential Homes - Ulinata, Ulinata; Miracella, Jessica; Napitupulu, Yolanda (Asian Journal of Community Services, 2024)
Lecturers and students of the Architecture Study Program at the Christian University of Indonesia together in partnership with Antheia and Fempire once again held a Community Service on Harapan Island by raising the title "Utilizing Waste from the Natural Resources of Harapan Island to Become Kitchen/Pantry Decoration Elements in Residential Homes.” This is the fourth Community Service activity on Harapan Island where the method that were used involved conducting socialization with the Harapan island’s housewives as participants with the approach involved providing instructional material from the speaker and then guiding the participants in practicing the material presented. The results showed that almost all participants were able to complete the products in form of table decorations for the pantry/kitchen as well as used bottles with shell ornaments added to them.